Economic Assessment of Biodiesel Production for Hungarian Farmers - Bai, Attila (Acta Agraria Debreceniensis, 2002)
Utilisation of oil of plant origin as a fuel is gaining acceptance in the European Union and elsewhere. Besides environmental protection, energy saving, and decreasing over-production of food. Additionally, the subsidisation of farmers and the development of rural sub-regions also contribute to its spread. This study specifically focuses on the direct effects biodiesel's raw materials and final products are now having on farmers, while reviewing and quantifying these effects. I have purposely restricted my analysis to these two elements of the biodiesel chain.The biodiesel chain seems to be a great method for improving the economic and social position of participant farmers in many ways. Presently, the profitability of raw materials’ production looks to be the crucal point in the chain, and could be strengthened best with intensive, habitat-specific agrotechnic. It would only be possible to reach a favourable profit margin for farmers if yields reach unrealistic averages or if there is a significant hike of the 2000 producer’s price in the oil plant branch.The main attraction of sunflower- and oilseed rape production lies in the stabilization of market conditions, which is not only gong to appear in oil plant branch but – thanks to the reduction of outputs – also in the cereal branches. Better economic safety for farmers may play a role at least on the same level as in plant production, which involves more risks than profit maximalization.The reduction of the prime cost of biodiesel could be possible through the direct combustion of the whole oilseed plant or its residues or electricity production using them. Whereas energy demand for biodiesel production is low (appr. 5%) but it needs subsidization and the prices of natural gas and electrical energy presently look favourable in Hungary. Additionally harvesting and baling of the residues is technically problematic, which is why their use may seem to be reasonable just over the middle or long term. Another possible factor of cost reduction could be the centralization of some partial operations, which needs serious financial resources to reduce amortization cost per product, provided there be several biodiesel projects near each other during establishment. Creation and operation of a logistical system could also be a good method for improving the viability of the biodiesel chain, in order to optimize transport schedule and distances. However there are also some organizational difficulties in this case.